2014
DOI: 10.1021/bm401720z
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Coassembly of Hydrogelators and Surfactants Based on Aromatic Peptide Amphiphiles

Abstract: The coassembly of small molecules is a useful means of increasing the complexity and functionality of their resultant supramolecular constructs in a modular fashion. In this study, we explore the assembly and coassembly of serine surfactants and tyrosine-leucine hydrogelators, capped at the N-termini with either fluorenyl-9-methoxycarbonyl (Fmoc) or pyrene. These systems all exhibit self-assembly behavior, which is influenced by aromatic stacking interactions, while the hydrogelators also exhibit β-sheet-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(134 citation statements)
references
References 93 publications
5
129
0
Order By: Relevance
“…Previously,b yu sing sub-gelation concentrations, we have observed that Fmoc-YL demonstrates ap ositive CD peak at approximately 305 nm, in addition to strong shorter wavelengths ignals centered around2 75 nm which may include a contribution from the tyrosine residues. [9] Upon increasing pregelation temperatures, positive peaks in the 275 and 305 nm regions invert to an egative signal ( Figure 3c), with the inversion point coinciding with the lowest relative mobility of fluorenyl and tyrosine residues observed by NMR spectroscopy (333-343K). Additionally,C Ds pectra of pre-gelation solutions at elevated temperatures ( Figure S4,S upporting Information) show that Fmoc-YLs olutions have an egative CD signal at relatively low temperatures (313-333 K) with intensity reduced at elevated temperatures (343 and 353 K).…”
Section: Resultsmentioning
confidence: 91%
“…Previously,b yu sing sub-gelation concentrations, we have observed that Fmoc-YL demonstrates ap ositive CD peak at approximately 305 nm, in addition to strong shorter wavelengths ignals centered around2 75 nm which may include a contribution from the tyrosine residues. [9] Upon increasing pregelation temperatures, positive peaks in the 275 and 305 nm regions invert to an egative signal ( Figure 3c), with the inversion point coinciding with the lowest relative mobility of fluorenyl and tyrosine residues observed by NMR spectroscopy (333-343K). Additionally,C Ds pectra of pre-gelation solutions at elevated temperatures ( Figure S4,S upporting Information) show that Fmoc-YLs olutions have an egative CD signal at relatively low temperatures (313-333 K) with intensity reduced at elevated temperatures (343 and 353 K).…”
Section: Resultsmentioning
confidence: 91%
“…proteins or peptide motifs) [28][29][30] In order to tailor suitable materials, we made use of a two-component co-assembly approach comprising a peptide based gelator (the structural element) and a surfactant-like molecule that presents carboxylate functionality to the surface of fibres 31 , enabling subsequent cross-linking upon exposure to divalent cations (Ca 2+ ) present in tissue culture media. Specifically, when fluorenyl-9-methoxycarbonyldiphenylalanine, Fmoc-F2 24,32,33 was co-assembled with surfactant-like Fmoc-serine (Fmoc-S), the polar serine side chains were presented at the surface of the fibres (Fig 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Noncovalent interactions are collectively strong enough to form highly organized self‐assembled 3D supramolecular structures with a dynamic error correction property . However, controlling the self‐assembly of a multicomponent system in one pot is rather challenging . In contrast, the Adams group reported the self‐sorting behavior of two molecules by regulating the solution pH .…”
Section: Figurementioning
confidence: 99%